Environmental switching during biofilm development in a cold seep system and functional determinants of species sorting. Issue 9 (19th January 2016) - Zhang, Weipeng; Tian, Renmao; Bo, Yang; Cao, Huiluo; Cai, Lin; Chen, Lianguo; Zhou, Guowei; Sun, Jin; Zhang, Xixiang; Al‐Suwailem, Abdulaziz; Qian, Pei‐Yuan
Abstract: The functional basis for species sorting theory remains elusive, especially for microbial community assembly in deep‐sea environments. Using artificial surface‐based biofilm models, our recent work revealed taxonomic succession during biofilm development in a newly defined cold seep system, the Thuwal cold seeps II, which comprises a brine pool and the adjacent normal bottom water (NBW) to form a metacommunity via the potential immigration of organisms from one patch to another. Here, we designed an experiment to investigate the effects of environmental switching between the brine pool and the NBW on biofilm assembly, which could reflect environmental filtering effects during bacterial immigration to new environments. Analyses of 16S rRNA genes of 71 biofilm samples suggested that the microbial composition of biofilms established in new environments was determined by both the source community and the incubation conditions. Moreover, a comparison of 18 metagenomes provided evidence for biofilm community assembly that was based primarily on functional features rather than taxonomic identities; metal ion resistance and amino acid metabolism were the major species sorting determinants for the succession of biofilm communities. Genome binning and pathway reconstruction of two bacterial species ( Marinobacter sp. and Oleispira sp.) further demonstrated metal ion resistance and amino acid metabolism as functional traits conferring the survival of habitat generalists in both the brine pool and NBW. The results of this study shed new light on microbial community assembly in special habitats and bridge a gap in species sorting theory. Abstract : See also the Perspective by Wagner‐Döbler